Structural Monitoring of a Drawbridge in Operation: Signal Analysis - Pedro J. S. C. P. Sousa; Susana Dias; Nuno Viriato Ramos; Job Santos Silva; Mário A. P. Vaz; Paulo J. Tavares; Pedro M. G. P. Moreira (Signals, 2025)
Monitoring large critical infrastructures is a highly complex and costly task. The use of a network of sensors to aid in the detection and identification of potential anomalies is therefore an important step towards easing maintenance effort while maintaining operational soundness. To address this challenge, a monitoring system was developed and installed in a seaport drawbridge. The structural parameters monitored during operation can be used to assess the bridge’s structural behavior. This provides the ability to identify potential anomalies that could lead to its failure at an early stage, allowing for the better planning of maintenance interventions, saving time and money. In this paper, the monitoring system will be presented and the employed signal identification and analysis methods will be described.